META ANALISIS LATIHAN DRILL DALAM MENINGKATKAN KETEPATAN PUKULAN SMASH ATLET BULUTANGKIS - Muhammad Hasbi Ash Shiddieqy; adrizal, mohd; Sukendro, Sukendro (LPPM Universitas Jambi, 2025)
The aim of this research is to re-analyze the use of the drill training method in improving the accuracy of badminton smash shots. The method used in this research is meta analysis. Research begins by formulating a research problem, exploring research results that are relevant for analysis. Data was collected by searching electronic journals via Google Scholar with the keywords